The Neogene-Quaternary geodynamic evolution of the central Calabrian Arc: A case study from the western Catanzaro Trough basin. (December 2016) - Brutto, F.; Muto, F.; Loreto, M.F.; Paola, N. De; Tripodi, V.; Critelli, S.; Facchin, L.
Highlights: Onshore and offshore geodynamic evolution of the central Calabrian Arc. Analysis of the role played by transcurrent and oblique-normal faults. Reactivation of fault systems as key element to understand the basin evolution. The new identified NE-trending normal fault affecting also recent sediments (i.e. western Ctanzaro trough). The geodynamic role of Catanzaro Trough as element of accommodation between northern and southern Calabrian Arc. Abstract: The Catanzaro Trough is a Neogene-Quaternary basin developed in the central Calabrian Arc, between the Serre and the Sila Massifs, and filled by up to 2000 m of continental to marine deposits. It extends from the Sant'Eufemia Basin (SE Tyrrhenian Sea), offshore, to the Catanzaro Basin, onshore. Here, onshore structural data have been integrated with structural features interpreted using marine geophysical data to infer the main tectonic processes that have controlled the geodynamic evolution of the western portion of the Catanzaro Trough, since Upper Miocene to present. The data show a complex tectonostratigraphic architecture of the basin, which is mainly controlled by the activity of NW–SE and NE–SW trending fault systems. In particular, during late Miocene, the NW-SE oriented faults system was characterized by left lateral kinematics. The same structural regime produces secondary fault systems represented by E-W and NE-SW oriented faults. The ca. E-W lineaments show extensional kinematics, which may have played an important role during the opening of the WNW–ESE paleo-strait; whereas the NE-SW oriented system represents the conjugate faults of the NW-SE oriented structural system, showing a right lateral component of motion. During the Piacenzian-Lower Pleistocene, structural field and geophysical data show a switch from left-lateral to right-lateral kinematics of the NW-SE oriented faults, due to a change of the stress field. This new structural regime influenced the kinematics of the NE-SW faults system, which registered left lateral movement. Since Middle Pleistocene, the study area experienced an extensional phase, WNW-ESE oriented, controlled mainly by NE-SW and, subordinately, N-S oriented normal faults. This type of faulting splits obliquely the western Catanzaro Trough, producing up-faulted and down-faulted blocks, arranged as graben-type system (i.e Lamezia Basin). The multidisciplinary approach adopted, allowed us to constrain the structural setting of the central Calabria segment. The joined onshore with offshore structural data analysis allowed us to image a more faithful geodynamic evolution of the Calabrian Arc, included in the wider geodynamic framework of the Mediterranean region Moreover, our results show the close correlation between the NE-SW and N-S normal fault systems and evidence of deformed Quaternary deposits. These findings are relevant to seismic hazard understanding in an area which is historically considered at the highest risk of earthquake and tsunami and where are present important infrastructures and cities.